Advance review on the exploitation of the prominent energy-storage element: Lithium. Part I: From mineral and brine resources - Choubey, Pankaj K.; Kim, Min-seuk; Srivastava, Rajiv R.; Lee, Jae-chun; Lee, Jin-Young (Minerals engineering, 2016)
•Critically reviewed various processes for the recovery of Li from minerals and brines.•Heat treatment is required for liberating Li from the mineral lattice before leaching.•Solar evaporation of brine is crucial for Li enrichment to make the process viable.•Precipitation is extensively applied for the separation and purification of Li as Li2CO3.•SX/IX/RO/adsorption is being explored as an alternative for process enhancement. Lithium (Li), an exceptional cathode material in rechargeable batteries, is an essential element in modern energy production and storage devices. The continuously increasing demand for lithium in these devices, along with their steady production, has led to the high economic importance of lithium, making it one of the strategically influential elements. The uneven distribution of mineral resources in the earth’s crust and the unequal concentration in brine and sea water reserves also causes lithium exploitation to be of critical importance. This situation requires the efficient processing of lithium resources either by the processing of minerals/brine/sea water or by the recycling of spent lithium-ion batteries. To explore new routes for the sustainable exploitation of lithium, it is imperative to review the methodologies that have already been studied and are currently in industrial practice. In this study, we present an overview of the processes investigated for the extraction, separation and recovery of lithium from not only a technological perspective but also from a chemical perspective. In Part I, this state-of-the-art review addresses the processing of lithium resources that currently contributes to the commercial exploitation of this energy-critical element. This review includes lithium recovery from mineral (spodumene, petalite, lepidolite, zinnwaldite) and brine resources. A deliberation of the mineralogical aspect along with a review of the extraction process of lithium minerals is sub-divided according to the chosen media, namely, chloride, sulfate and carbonate, for their conversion into a leachable form, whereas the division of aqua-based resources is based on the lithium concentration. In the discussion, the advantages and/or disadvantages, problems and prospects of the processes are also summarized. We believe this article can contribute to improving the extraction and recovery processes of lithium toward the sustainability of this critical element and can provide future research directions.